Structure of Guarantees in Business Transactions in Indonesia in Indonesian Law - Nasution, Emmi Rahmiwita (Westscience Press, 2023)
Using a quantitative analytic methodology, this study examines how assurances are arranged in economic transactions inside Indonesian legal frameworks. Based on a review of a variety of datasets, the study reveals that personal guarantees are the most common kind, followed by bank and corporate guarantees. Different industries' patterns of guarantee utilization show different frequency of use, with the real estate and finance sectors showing a greater reliance. While 75% of compliance is considered satisfactory, there are cases of non-compliance due to ambiguity in legal terms. These results highlight the need for sector-specific laws, improved legal clarity, and ongoing stakeholder education. This study offers policymakers and stakeholders useful information to improve the guarantee structure and provide a flexible and robust legal framework for business dealings in Indonesia.